Isolated and solitary splenic metastasis detected by positron emission tomography in a patient with malignant melanoma: Case report and review of the literature - Sen, Cenk Ahmet; Kargi, Aysegul; Kaya, Vildan; Tanriverdi, Ozgur (Contemporary Oncology/Współczesna Onkologia, 2013)
Splenic metastasis from malignant melanoma is an extremely rare occurrence and is most often reported during autopsy. As in other solid tumors, splenic metastasis is usually part of multiple organ metastases in melanoma and is rarely an isolated or solitary mass. As the use of positron emission tomography /computed tomography and imaging techniques become more common, splenic metastases are seen more often than before. Even though it is a commonly known fact that positron emission tomography/computed tomography is no help during primary staging and patient relations in malignant melanoma, several studies and meta-analyses have proven that it is more specific, sensitive and accurate to identify metastases than raditional methods. Therefore, using techniques with high specificity and accuracy rates such as positron emission tomography/computed tomography in the diagnosis of splenic metastasis in patients with malignant melanoma will increase the survival rate with an earlier splenectomy. We report the case of a 35-year-old male patient with cutaneous malignant melanoma whose splenic metastasis was detected with positron emission tomography/computed tomography. This article describes, with reference to the literature, a malignant melanoma case, which presented with splenomegaly and solitary mass lesion and was diagnosed as metastasis by splenectomy after positron emission tomography/computed tomography.